Congenital Anomalies of the Penis - Fahmy, Mohamed (Springer International Publishing : Imprint: Springer, 2017)
This book provides comprehensive but concise data for congenital diseases of the penis, explaining the embryological and anatomical background, incidence, historical background, investigation approaches, imaging and management of each condition. The book is organised in themed parts, starting from embryology and normal anatomy and examining anomalies for each anatomical part: prepuce, penis, urinary meatus, penile urethra with a final part of acquired penile diseases with congenital background. With clear illustrations in each chapter to explain each condition in detail, online animations for the difficult and complex cases are also provided. Practitioners in the field of pediatric urology and surgery will find this highly readable book particularly valuable. The author is a pioneer pediatric surgeon with over 30 years' experience in the field of genitourinary anomalies.
Keywords: Medicine.; Pediatrics.; Pediatric surgery.; Urology.; elektronické knihy; electronic books